Long non-coding RNA SPRY4-IT1 promotes proliferation and invasion by acting as a ceRNA of miR-101-3p in colorectal cancer cells - Jianguang Jin; Zhijie Chu; Pengfei Ma; Yuanpu Meng; Yanhui Yang (Tumor Biology)
Long non-coding RNAs are associated with a spectrum of biological processes such as gene regulation on transcriptional and post-transcriptional levels. Increasing evidence indicates that SPRY4-IT1 plays an important role in carcinogenesis, and the mechanisms whereby SPRY4-IT1 induces colorectal carcinoma progression remain largely unknown. The aim of this study is to evaluate the expression and function of SPRY4-IT1 in colorectal carcinoma. In this study, we analyzed SPRY4-IT1 expression levels in a series of colorectal carcinoma patients by quantitative reverse transcription polymerase chain reaction. Knockdown of SPRY4-IT1 by RNA interference was performed to explore its roles in cell proliferation, migration, and invasion. Our results found that SPRY4-IT1 was upregulated in human primary colorectal carcinoma tissues. Knockdown of SPRY4-IT1 inhibited colorectal carcinoma cell proliferation, migration, and invasion. Moreover, we confirmed that the expression of epithelial–mesenchymal transition–related genes was modulated through alteration of SPRY4-IT1 expression. SPRY4-IT1 could negatively regulate the expression of miR-101-3p in colorectal carcinoma cells. The bioinformatics prediction revealed putative miR-101-3p binding sites within SPRY4-IT1 transcripts. Above all, knockdown of SPRY4-IT1 could represent a rational therapeutic strategy for colorectal carcinoma.